CT material decomposition with contrast agents: Single or multiple spectral photon-counting CT scans? : A simulation study - Sawall, Stefan; Baader, Edith; Trapp, Philip; Kachelrieß, Marc (Medical physics, 2025)
Purpose With the widespread introduction of dual energy computed tomography (DECT), applications utilizing the spectral information to perform material decomposition became available. Among these, a popular application is to decompose contrast-enhanced CT images into virtual non-contrast (VNC) or virtual non-iodine images and into iodine maps. In 2021, photon-counting CT (PCCT) was introduced, which is another spectral CT modality. It allows for scans with more than two different detected spectra. With these systems, it becomes possible to distinguish more than two materials. It is frequently proposed to administer more than one contrast agent, perform a single PCCT scan, and then calculate the VNC images and the contrast agent maps. This may not be optimal because the patient is injected with a material, only to have it computationally extracted again immediately afterwards by spectral CT. It may be better to do an unenhanced scan followed by one or more contrast-enhanced scans. The main argument for the spectral material decomposition is patient motion, which poses a significant challenge for approaches involving two or more temporally separated scans. In this work, we assume that we can correct for patient motion and thus are free to scan the patient more than once. Our goal is then to quantify the penalty for performing a single contrast-enhanced scan rather than a clever series of unenhanced and enhanced scans. In particular, we consider the impact on patient dose and image quality. Methods We simulate CT scans of three differently sized phantoms containing various contrast agents. We do this for a variety of tube voltage settings, a variety of patient-specific prefilter (PSP) thicknesses and a variety of threshold settings of the photon-counting detector with up to four energy bins. The reconstructed bin images give the expectation values of soft tissue and of the contrast agents. Error propagation of projection noise into the images yields the image noise. Dose is quantified using the total CT dose index (CTDI) value of the scans. When combining multiple scans, we further consider all possible tube current (or dose) ratios between the scans. Material decomposition is done image-based in a statistical optimal way. Error propagation into the material-specific images yields the signal-to-noise ratio at unit dose (SNRD). The winning scan strategy is the one with the highest total SNRD, which is related to the SNRD of the material that has the lowest signal-to-noise ratio (SNR) among the materials to decompose into. We consider scan strategies with up to three scans and up to three materials (water W, contrast agent X and contrast agent Y). Results In all cases, those scan strategies yield the best performance that combine differently enhanced scans, for example, W+WX, W+WXY, WX+WXY, W+WX+WY, with W denoting an unenhanced scan and WX, WY and WXY denoting X-, Y-, and X-Y-enhanced scans, respectively. The dose efficiency of scans with a single enhancement scheme, such as WX or WXY, is far lower. The dose penalty to pay for these single enhancement strategies is about two or greater. Our findings also apply to scans with a single energy bin and thus also to CT systems with conventional, energy-integrating detectors, that is, conventional DECT. Dual source CT (DSCT) scans are preferable over single source CT scans, also because one can use a PSP on the high Kilovolt spectrum to better separate the detected spectra. For the strategies and tasks considered here, it does not make sense to simultaneously scan with two different types of contrast agents. Iodine outperforms other high Z elements in nearly all cases. Conclusions Given the significant dose penalty when performing only one contrast-enhanced scan rather than a series of unenhanced and enhanced scans, one should consider avoiding the single-scan strategies. This requires to invest in the development of accurate registration algorithms that can compensate for patient and contrast agent motion between separate scans.